MR Elastography demonstrates reduced white matter shear stiffness in early-onset hydrocephalus - M.E. Wagshul; J.P. McAllister; D.D. Limbrick Jr.; S. Yang; W. Mowrey; J.T. Goodrich; A. Meiri; D.M. Morales; A. Kobets; R. Abbott (NeuroImage: Clinical, 2021)
Introduction: Hydrocephalus that develops early in life is often accompanied by developmental delays, headaches and other neurological deficits, which may be associated with changes in brain shear stiffness. However, noninvasive approaches to measuring stiffness are limited. Magnetic Resonance Elastography (MRE) of the brain is a relatively new noninvasive imaging method that provides quantitative measures of brain tissue stiffness. Herein, we aimed to use MRE to assess brain stiffness in hydrocephalus patients compared to healthy controls, and to assess its associations with ventricular size, as well as demographic, shunt-related and clinical outcome measures. Methods: MRE was collected at two imaging sites in 39 hydrocephalus patients and 33 healthy controls, along with demographic, shunt-related, and clinical outcome measures including headache and quality of life indices. Brain stiffness was quantified for whole brain, global white matter (WM), and lobar WM stiffness. Group differences in brain stiffness between patients and controls were compared using two-sample t-tests and multivariable linear regression to adjust for age, sex, and ventricular volume. Among patients, multivariable linear or logistic regression was used to assess which factors (age, sex, ventricular volume, age at first shunt, number of shunt revisions) were associated with brain stiffness and whether brain stiffness predicts clinical outcomes (quality of life, headache and depression). Results: Brain stiffness was significantly reduced in patients compared to controls, both unadjusted (p ≤ 0.002) and adjusted (p ≤ 0.03) for covariates. Among hydrocephalic patients, lower stiffness was associated with older age in temporal and parietal WM and whole brain (WB) (beta (SE): −7.6 (2.5), p = 0.004; −9.5 (2.2), p = 0.0002; −3.7 (1.8), p = 0.046), being female in global and frontal WM and WB (beta (SE): −75.6 (25.5), p = 0.01; −66.0 (32.4), p = 0.05; −73.2 (25.3), p = 0.01), larger ventricular volume in global, and occipital WM (beta (SE): −11.5 (3.4), p = 0.002; −18.9 (5.4), p = 0.0014). Lower brain stiffness also predicted worse quality of life and a higher likelihood of depression, controlling for all other factors. Conclusions: Brain stiffness is reduced in hydrocephalus patients compared to healthy controls, and is associated with clinically-relevant functional outcome measures. MRE may emerge as a clinically-relevant biomarker to assess the neuropathological effects of hydrocephalus and shunting, and may be useful in evaluating the effects of therapeutic alternatives, or as a supplement, of shunting.